Sponge city construction and population health - Li, Yue (Frontiers in Public Health, 2024)
Introduction: This paper focuses on the construction of sponge cities and their effects on population health. Sponge cities in China both solve stormwater problems and are a systemic transformation in the urban construction paradigm, addressing related issues arising from high-speed urbanization. Whether sponge city construction in China can promote population health has received scant attention. Most previous studies have focused on urban environments and population health, with few exploring the potential effects on population health caused by urban environment changes due to urban policies. This study hypothesizes that sponge city construction improves the urban environment, and thus, population health. Methods: Using panel data from 119 prefecture-level cities between 2011-2019 and the China Labor-force Dynamics Survey (CLDS), based on China's sponge city pilot policy, a quasinatural experiment is conducted using Difference-in-Differences (DID) model to identify the health effects of the sponge city policy. Results: The findings shows that sponge city pilot policy not only reduced ecological environment pollution and promoted the quality of build environment, but also significantly improved population health by 10.4%. This mechanism is mainly due to the restorative effects of the built environment. Discussion: The health effects vary across city administrative levels, and especially among non-older adult and local populations. Compared with the cities at higher administrative level, the health effect in lower administrative level is significantly positive, indicating that there is a diminishing marginal effect of sponge city construction. This study extends the causal identification chain of the impact of urban environment on population health to urban policies and provide insights into policy objectives for sponge city construction.